CD44 alternative splicing in gastric cancer cells is regulated by culture dimensionality and matrix stiffness. (August 2016) - Branco da Cunha, Cristiana; Klumpers, Darinka D.; Koshy, Sandeep T.; Weaver, James C.; Chaudhuri, Ovijit; Seruca, Raquel; Carneiro, Fátima; Granja, Pedro L.; Mooney, David J.
Abstract: Two-dimensional (2D) cultures often fail to mimic key architectural and physical features of the tumor microenvironment. Advances in biomaterial engineering allow the design of three-dimensional (3D) cultures within hydrogels that mimic important tumor-like features, unraveling cancer cell behaviors that would not have been observed in traditional 2D plastic surfaces. This study determined how 3D cultures impact CD44 alternative splicing in gastric cancer (GC) cells. In 3D cultures, GC cells lost expression of the standard CD44 isoform (CD44s), while gaining CD44 variant 6 (CD44v6) expression. This splicing switch was reversible, accelerated by nutrient shortage and delayed at lower initial cell densities, suggesting an environmental stress-induced response. It was further shown to be dependent on the hydrogel matrix mechanical properties and accompanied by the upregulation of genes involved in epithelial-mesenchymal transition (EMT), metabolism and angiogenesis. The 3D cultures reported here revealed the same CD44 alternative splicing pattern previously observed in human premalignant and malignant gastric lesions. These findings indicate that fundamental features of 3D cultures – such as soluble factors diffusion and mechanical cues – influence CD44 expression in GC cells. Moreover, this study provides a new model system to study CD44 dysfunction, whose role in cancer has been in the spotlight for decades.